Controlled synthesis of Ag-doped CuO nanoparticles as a core with poly(acrylic acid) microgel shell for efficient removal of methylene blue under visible light - Iqbal, Shahid; Javed, Mohsin; Bahadur, Ali; Qamar, Muhammad Azam; Ahmad, Madiha; Shoaib, Muhammad; Raheel, Muhammad; Ahmad, Naveed; Akbar, Muhammad Bilal; Li, Hao (Journal of materials science. Materials in electronics, 2020)
Nowadays, constructing a narrow bandgap nanocomposite photocatalyst that can degrade contamination under visible light is critical but challenging. In this report, poly (acrylic acid) microgel (PAA) based nanocomposites (Ag@CuO/PAA NC) were constructed via free radical solution polymerization by varying the concentration of silver-doped copper oxide nanoparticles (Ag@CuO NPs) from 0 to 12%. As prepared Ag@CuO and Ag@CuO/PAA were characterized by X‐ray diffraction spectroscopy, scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray and X-ray photoelectron spectroscopy. The size of Ag@CuO NPs was found to be 30–50 nm. The photocatalytic activity of CuO is increased by Ag doping and C3 NPs show the best photodegradation of methylene blue (MB). Then, 4% of Ag@CuO nanoparticles were incorporated into PAA microgel, the resultant nanocomposite showed a drastic increase in photodegradation of MB. Ag@CuO/PAA NC completely degraded dye in only 30 min which was degraded up to 65% in 60 min. by Ag@CuO NPs. The successful combination of PAA with Ag@CuO boosts the photocatalytic activity because microgel provides a large surface to adsorb pollutants. Ag@CuO/PAA NC reused successfully for photodegradation of dye due to the recycling ability of microgels. This study gives a good insight into planning a significant visible‐light‐driven photocatalyst for environmental remediation.